2012
DOI: 10.1200/jco.2012.30.15_suppl.e18043
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of non-small cell lung cancer in females with gefitinib therapy: An experience from eastern India.

Abstract: e18043 Background: Non-small cell lung carcinoma is usually an incurable disease with average overall survival of 7-9 months. But studies in recent years have shown that adenocarcinoma in nonsmokers with epidermal growth factor receptor (EGFR) positivity has shown disease control for longer duration. Female patients with adenocarcinoma where EGFR is positive show higher response rate with EGFR blocker. In eastern India, lung cancer contributes 21.3% of all cancers and female lung cancer contributes about 20% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There have been very few studies involving Indian lung cancer patients response to tyrosine kinase inhibitors [27,28] & these studies showed some benefit of using TKIs. These studies didn't include the genetic evaluations of the tumour samples before initiation of the anti-EGFR treatment & therefore those results were based on patient population that has not been selected using genetic evaluations of the tumor samples.…”
Section: Introductionmentioning
confidence: 99%
“…There have been very few studies involving Indian lung cancer patients response to tyrosine kinase inhibitors [27,28] & these studies showed some benefit of using TKIs. These studies didn't include the genetic evaluations of the tumour samples before initiation of the anti-EGFR treatment & therefore those results were based on patient population that has not been selected using genetic evaluations of the tumor samples.…”
Section: Introductionmentioning
confidence: 99%